Strategi Pemasaran Efektif dalam Meningkatkan Daya Saing Bank Syariah di Era Digital - Zuhrinal M. Nawawi; Aulia Syahfitri (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This research uses a qualitative method to examine effective marketing strategies implemented by Islamic banks in enhancing competitiveness in the digital era. Amid increasingly intense competition in the financial industry and rapid technological advancements, Islamic banks are required to adapt and utilize various digital platforms as marketing tools. This study focuses on analyzing digital marketing strategies such as the use of social media, mobile banking, and content marketing to build brand awareness and customer loyalty. Data were collected through in-depth interviews with Islamic banking practitioners and observation of their digital marketing activities. The findings reveal that integrating sharia values with digital technology creates a unique, relevant, and highly competitive marketing approach. Furthermore, the ability of Islamic banks to understand the needs of the millennial and Gen Z generations is a key factor in expanding their market share. Therefore, adaptive, innovative, and value-based marketing strategies are essential foundations for facing the digital era.